2020
DOI: 10.1371/journal.pone.0235599
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of percutaneous transthoracic needle biopsy (PTNB) of the lung and risk of PTNB-related severe pneumothorax: A nationwide population-based study

Abstract: Background As percutaneous transthoracic needle biopsy (PTNB) of the lung is a well-established diagnostic method for the evaluating pulmonary lesions, evidence of safety based on representative data is limited. This study investigated the practice patterns of PTNB of the lung and assessed the incidence and risk factors of PTNB-related severe pneumothorax in Korea. Methods We used a national-level health insurance database between January 1, 2007 and December 31, 2015. Patients who underwent PTNB of the lung w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Based on clinical experience and a literature review, we estimated that the risk scoring system for pneumothorax achieved a 70% sensitivity and a 90% speci city. The average prevalence of pneumothorax was approximately 15% in previous studies (2,4,12) . We chose α = 0.05 and maximum marginal error of estimate = 5%.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Based on clinical experience and a literature review, we estimated that the risk scoring system for pneumothorax achieved a 70% sensitivity and a 90% speci city. The average prevalence of pneumothorax was approximately 15% in previous studies (2,4,12) . We chose α = 0.05 and maximum marginal error of estimate = 5%.…”
Section: Discussionmentioning
confidence: 86%
“…Pneumothorax is a common but potentially dangerous complication. In previous studies, the average rate of pneumothorax episodes was reported to range from 1.1 to 29.8% (2,4) , while the development of severe pneumothorax post-biopsy requiring intervention occurred in 1%-14.2% of patients undergoing CT-guided PTNB (2) . The risk factors for pneumothorax have been less studied (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Percutaneous transthoracic needle lung biopsy (PTNB) is a well-established, minimally invasive procedure for evaluating lung abnormalities with excellent diagnostic accuracy and a low incidence of major complications [ 11 , 12 ]. According to previous studies, age can be a risk factor for complications, and other potential factors include emphysema, large needle, small lesions, increased lesion depth, and increased pleural passage [ 11 , 13 , 14 ]. However, few studies on the accuracy and safety of PTNB in patients 80 years and older [ 15 , 16 ] have been published, and moreover they fail to cover the diagnostic failure rates and their risk factors.…”
Section: Introductionmentioning
confidence: 99%